The population status, habitat use and seasonal diet of African elephant (Loxodonta africana) in Majete Wildlife Reserve, Malawi - Forrer, Frances Ann (Stellenbosch : Stellenbosch University, 2017)
Thesis (MScConsEcol)--Stellenbosch University, 2017.